4x - 2 = 2x + 8
2x -2 = 8
2x = 10
x = 5
4(5)-2 = 2(5)+8
20-2 = 10+8
18 = 18
Answer:
The last one right
Step-by-step explanation:
Divide by L both sides
Answer:
I think its 71
Step-by-step explanation:
Well the average between -3 -2 and -1 seems to be -2, so all i do is 95-24 and you get 71, either that or 65. I highly think its 71 though
X² + 6x -12 = 0
x = <u>-(6) +/- √((6)² - 4(1)(-12))</u>
2(1)
x = <u>-6 +/- √(36 + 48)</u>
2
x = <u>-6 +/- √(84)
</u> 2<u>
</u>x = <u>-6 +/- 2√(21)
</u> 2<u>
</u>x = -3 <u>+</u> √(21)
x = -3 + √(21) x = -3 - √(21)